2018
DOI: 10.3390/ijms19061697
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analyses of Anatomical Structure, Phytohormone Levels, and Gene Expression Profiles Reveal Potential Dwarfing Mechanisms in Shengyin Bamboo (Phyllostachys edulis f. tubaeformis)

Abstract: Moso bamboo (Phyllostachys edulis) is one of the most important bamboo species in China and the third most important plant species for timber production. However, the dwarf variant of moso bamboo, P. edulis f. tubaeformis (shengyin bamboo), which has shortened internodes, is not well studied. We used anatomical, hormonal, and transcriptomic approaches to study internode shortening and shoot growth in dwarf shengyin and wild moso bamboo. Phenotypic and anatomical observations showed that dwarfing in shengyin ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 55 publications
2
27
0
Order By: Relevance
“…Exogenous GA 3 application enhanced internode cell elongation in pea that the dwarf cultivar responds positively to exogenous GA 3 [82]. Furthermore, other studies have shown that GA 3 can promote cell elongation in internode tissue and act as regulators of stem elongation [83,84]. GA 3 induced cell elongation should have great significance to rice plants, which in turn develop a low-sensitivity pathway in response to high hormone levels [85].…”
Section: Discussionmentioning
confidence: 98%
“…Exogenous GA 3 application enhanced internode cell elongation in pea that the dwarf cultivar responds positively to exogenous GA 3 [82]. Furthermore, other studies have shown that GA 3 can promote cell elongation in internode tissue and act as regulators of stem elongation [83,84]. GA 3 induced cell elongation should have great significance to rice plants, which in turn develop a low-sensitivity pathway in response to high hormone levels [85].…”
Section: Discussionmentioning
confidence: 98%
“…The total number of bamboo nodes may be determined before shoots are unearthed, and the growth rate of each internode determines the overall growth rate of the bamboo (Wang et al, 2019). Previous studies have focused on the rapid growth period of the bamboo culm (Li et al, 2018; Wang et al, 2018), but there have been limited studies on the initiation stage of stem elongation, which occurs after the total number of bamboo nodes has formed. To explore the key regulatory genes for the growth of moso bamboo, samples of bamboo shoots at the early growth‐stage were collected from the Agricultural Garden of Anhui Agricultural University in Hefei, Anhui Province, China.…”
Section: Methodsmentioning
confidence: 99%
“…Genes for cellulose and lignin biosynthesis pathways, hormone biosynthesis, and signal transduction were significantly expressed in the internodes of wild and shengyin bamboo. Cell wall expansion, phytohormone signaling control, and phytohormone signaling were shown SRP133731 Wang et al, 2018 The alternative splicing mechanism in transcriptomes was studied. Genes (36.17%) undergo alternative splicing, which was associated with gene characteristics and gene expression.…”
Section: Major Findings Accession Number Referencesmentioning
confidence: 99%
“…Raw sequences of moso bamboo transcriptomes are publicly available in Sequence Read Archive database at the National Center for Biotechnology Information (http://www.ncbi.nlm.nih.gov/sra), European Molecular Biology Laboratory, and in the BambooNET and GigaScience (http://gigadb.org/) databases. Recent transcriptome studies in moso bamboo illustrate the roles of endogenous hormones in culm development and identified many biological pathways related to cell wall biosynthesis, the flowering process, the shoot fast growth, and their role under abiotic stress (Cheng, Hou, et al, 2018; Li, Shi, et al, 2018; Wang et al, 2018). A coexpression network was established for flower development, and TFs, transposable elements, and noncoding RNA profiles were identified.…”
Section: Development Of Genomic Resources For Identifying Genes Undermentioning
confidence: 99%